PETROLOGY AND ORIGIN OF PLAGIOGRANITES FROM THE DAĞKÜPLÜ (ESKİŞEHİR) OPHIOLITE ALONG THE İZMİR-ANKARA-ERZİNCAN SUTURE ZONE, TURKEY - Sarıfakıoğlu, Ender (Ofioliti, 2007)
The İzmir-Ankara-Erzincan Suture Zone (IAESZ) formed through the closure of the northern branch of the Neotethyan Ocean that once separated the Sakarya Continent and the Anatolide-Tauride Platform and the subsequent collision of these two continental blocks during Late Cretaceous-Paleocene time. Mafic-ultramafic rocks representing oceanic lithosphere, metamorphic sole rocks, and ophiolitic mélange comprising oceanic and continental fragments and continental margin metamorphic and sedimentary rocks are preserved along the IAESZ. A northward dipping subduction zone developed within the İzmir-Ankara-Erzincan Ocean, a northern branch of Neotethyan Ocean, in the Early Cretaceous. The suprasubduction zone (SSZ) ophiolites formed in this intra-oceanic setting. The Dağküplü Ophiolite was, like other ophiolite nappes in the region, thrust over the southern Anatolide-Tauride Platform. The Dağküplü Ophiolite, exhibiting an incomplete and inverted ophiolite suite, consists mostly of refractory peridotites (harzburgite and dunite) representing mantle unit and lesser dunite and wehrlite cumulates, pyroxenites, and massive-layered gabbros. The plagiogranite volumetrically constitutes about 10% of the entire ophiolitic rocks. Petrographic and geochemical data suggest that plagiogranites were generated from TiO2-poor cumulate gabbros by fractional crystallization at a suprasubduction zone spreading center.